Pengembangan Perangkat Pembelajaran Biologi Terintegrasi Karakter dan Materi Pendidikan Lingkungan Hidup (PLH) - RIMAS ALDILLA PUTRI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2012)
Abstract— The developing of integrated character and environment education materials learning resources is the researches with the purpose are: (1) producing the eligibility learning resources to implement, (2) describing the result of mastery concept, (3) describing the valuation of character, and (4) describing the students response. This developing refers to 4D Model. The results of this research are: (1) the eligibility of learning resources to implement, (2) the mastery concept has been completed in 88,08 %, (3) the valuation of careness about environmental in score 3,47, communicative and creative character in score 3,59, and (4) the students response in score 3,39. Keywords: learning resources, character and environmental education.